President's Message: Transitions: New Roles — New commitments - Hay, Vija (Operating Room Nurses Association of Canada Journal, 1995)
As I begin my term as President of ORNAC, I reﬂect on the past and the future, and therefore my words from the closing ceremonies at the National Conference in Vancouver may be appropriate to repeat.